A comparison of the different features of quadripolar left ventricular pacing leads to deliver cardiac resynchronization therapy. (2nd September 2017) - Antoniadis, Antonios P.; Behar, Jonathan M.; Sieniewicz, Ben; Gould, Justin; Niederer, Steven; Rinaldi, Christopher A.
ABSTRACT: Introduction : Cardiac Resynchronization therapy (CRT) improves the quality of life and reduces morbidity and mortality of certain patients with heart failure. However, not all patients respond positively after CRT and about one third of cases do not experience benefit. Suboptimal biventricular pacing may account for this and quadripolar left ventricular (LV) leads have emerged in the last years to address issues relating to inadequate delivery of CRT. Areas covered : This review article concisely summarizes the main technical characteristics of the quadripolar LV leads either currently available in the market today or under final stages of development. Focus is given in recent advancements in the area and challenging aspects and controversies, future implications as well as opportunities for further development. Expert commentary : Quadripolar LV pacing leads have now become the standard of care in CRT. Currently a multitude of lead options is available to the clinician. The selection process of the most appropriate lead is far from the 'one size fits all' concept. Further development of quadripolar LV leads is currently ongoing and it is anticipated to contribute towards the release of more technologically advantageous leads which will enable the delivery of optimal CRT therapy with the lowest rate of complications.